The Analysis of Leverage, Return on Assets, and Firm Size on Tax Avoidance - Astriyani Sandya Paramita; Muhammad Noor Ardiansah; Raissa Arham Delyuzar; Arif Dzulfikar (Universitas Negeri Semarang, 2022)
Purpose : The study aims to analyze the effect of leverage, return on assets, and firm size on tax avoidance in Property and Real Estate Companies listed on the Indonesia Stock Exchange (IDX) for the 2010-2016 period. Method : The population in this research are real estate companies listed on the Indonesia Stock Exchange. The sample selection process in this research used a purposive sampling method. Testing the effect of leverage, return on assets, and firm size on tax avoidance is done using multiple linear regression analysis models. Findings : Based on the results of the study, the CETR level is positively and significantly influenced by the level of return on assets and company size. Meanwhile, CETR is negatively and significantly affected by the level of leverage. Novelty : In this study, the sample is focused on property and real estate companies listed on the Indonesia Stock Exchange based on sharia stocks because related research has not been widely studied, so it is necessary to do more about tax avoidance in sharia stocks. Keywords : Tax Avoidance; Return on Assets; Leverage; Firm Size